Development of Hotel System Learning Application: Te Hotel Simulator - Endah Fitriyani; Ilma Indriasri Pratiwi; B. Erfransyah Levi Darmawan (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
Hotel system learning at the secondary and higher education levels in Indonesia is currently still using manual systems, which is not suitable for the current digital technological development used by the hotel industry. Background Problems: Some of the current hotel information system learning simulation software that has been developed tend to be too expensive and unaffordable for educational institutions in Indonesia. Novelty: The purpose of developing this application is to be used in the world of tourism and hospitality education in Indonesia. Research Methods: Research and Development approach we use to develop this application. Finding/Results: This study develops a hotel information system learning application called TE Hotel Simulator that uses a role-playing system for its users. The existing roles are as a reservation officer, front office clerk, and housekeeping officer. This application works with the Android operating system that can be accessed using a mobile phone or tablet. This application is supported by a backend system through the website www.tesim.id. Conclusion: TE Hotel Simulator is still in beta version and should be developed into a more interactive application so the learning process could gain more experience for students